What Would it Cost to Coach Every New Principal? An Estimate Using Statewide Personnel Data - Lochmiller, Chad R. (Education Policy Analysis Archives, 2014)
In this paper, I use Levin and McEwan’s (2001) cost feasibility approach and personnel data obtained from the Superintendent of Public Instruction to estimate the cost of providing coaching support to every newly hired principal in Washington State. Based on this descriptive analysis, I estimate that the cost to provide leadership coaching to every newly hired principal as an induction support would range between 153,000 and 845,000 per year representing a per pupil cost between 4.01 and 12.35, respectively, depending on the amount each leadership coach receives in compensation. A more conservative approach that provides coaching support only to newly hired principals working in high poverty schools would cost the state between 143,975 and 443,000 per year representing a per pupil cost between 4.20 and 12.92, respectively, depending on the amount each leadership coach receives in compensation. Implications for coaching and principal professional development are discussed within the context of policy decisions. In particular, the article considers whether coaching is a financially feasible professional development strategy and how new information about the per pupil cost of coaching might better inform ongoing policy discussions related to leadership coaching.